Peranan Dr. A.K Gani dalam Masa Revolusi Fisik Sumatera Selatan (1945-1949) - Wijaya, Tomy; Aulia, Jessica Amanda; Amelia, Siska; Mayasari, Sarmi; Yusuf, Syafruddin; Yati, Risa Marta (Universitas Galuh, 2025)
The research aims to analyse the role of Dr Adnan Kapau Gani (A.K. Gani) during the Physical Revolution in South Sumatra (1945-1949). Through a historical approach, the research explores his contributions to the independence struggle, including community organising and natural resource diplomacy, particularly oil. This method involves the process of studying, explaining and critically analysing various data and relics from the past. The results show that he played a role in the military, economy and diplomacy. He played an important role in community mobilisation and the expropriation of resources from the colonialists, as well as in the formation of organisations that supported the struggle for independence. In military terms, he became a resistance leader and coordinated battle strategies against the Dutch. One of them was the Five Days and Five Nights Battle (1-5 January 1947). In addition, he ensured the efficient distribution of war logistics. Furthermore, as Minister of Prosperity, he utilised South Sumatra's natural resources such as oil, rubber, coal to support the struggle for independence and established economic cooperation with the American-Indonesian Corporation to break the Dutch economic blockade. In addition, he also played a role in maintaining communication between the central and regional governments, and was active in international diplomacy to fight for the recognition of the sovereignty of the Republic of Indonesia. It can be concluded that Dr A.K. Gani was a leader of the Indonesian government.